Time‐restricted versus standard‐duration immunosuppression after allogeneic hematopoietic stem cell transplantation: Results of the prospective randomized HOVON‐96 trial - Annoek E. C. Broers; Ellen Meijer; Bronno van der Holt; Cornelis N. de Jong; Erfan Nur; Geerte L. van Sluis; Goda Choi; Michel van Gelder; Johan A. Maertens; Jürgen Kuball; Dries Deeren; Heleen A. Visser‐Wisselaar; et al. (HemaSphere)
Abstract Cyclosporine A combined with mycophenolate mofetil (CsA/MMF) has become an established regimen for the prevention of graft‐versus‐host disease (GVHD) following non‐myeloablative (NMA) allogeneic hematopoietic stem cell transplantation (alloHSCT). However, the optimal duration of immunosuppression (IS) has not yet been defined and overtreatment is of concern. We hypothesized that time‐restricted IS with CsA/MMF would increase the proportion of patients with non‐severe GVHD compared to standard‐duration IS, thereby resulting in reduction of the relapse rate and improvement of progression‐free survival (PFS) and overall survival (OS). In a prospective randomized, multicenter, phase III trial, patients were allocated (1:1) to standard or time‐restricted IS. A total of 389 patients were randomized, of whom 369 were transplanted (184 vs. 185 patients). The primary endpoint, the proportion of patients with non‐severe GVHD defined as acute GVHD grades I–II without gut involvement or chronic GVHD not requiring systemic treatment within 180 days posttransplant, was 23% after standard‐duration IS versus 24% after time‐restricted IS (odds ratio: 1.02; 95% confidence interval (CI) 0.63–1.66, p = 0.92). The cumulative incidence of grade III–IV acute GVHD at 6 months posttransplant was not significantly different (14% vs. 18%; p = 0.20). The two‐year cumulative incidence of chronic extensive GVHD was 50% versus 46% (p = 0.62). There were no significant differences in the rates of relapse/progression, non‐relapse mortality, PFS, OS, and GVHD‐free, relapse‐free survival. Time‐restricted IS with CsA/MMF did not increase the proportion of patients with non‐severe GVHD, and secondary outcomes were not different compared to standard‐duration IS following NMA‐matched alloHSCT.